Microhardness, laser damage threshold and SHG efficiency studies of potassium dihydrogen phosphate crystals doped with L-arginine amino acid - Kostenyukova, E.I.; Bezkrovnaya, O.N.; Kolybaeva, M.I.; Dolzhenkova, E.F.; Kovalenko, N.O.; Kanaev, A.; Pritula, I.M. (Functional Materials, 2016)
Potassium dihydrogen phosphate (KDP) single crystals doped with L-arginine (L-arg) amino acid (with a concentration of 0.3 to 1.4 wt. % in the solution) were grown onto a point seed by the temperature reduction method. The effect of L-arg molecules on the strength properties {100} of KDP crystal were studied. Doping of KDP crystals with L-arg molecules raised the laser damage threshold in comparison with pure KDP in the sector {101}. There were defined the ranges of L-arg concentration where the microhardness and bulk laser damage threshold of KDP:L-arg crystals were higher in the growth sectors as compared with pure KDP. It was found that the efficiency of second harmonic generation in KDP:L-arg (1.4 wt.% of L-arg) exceeded the corresponding characteristic of pure KDP by ~ 2.5 times.